Manajemen Sarana Pendididkan Dalam Peningkatan Belajar Siswa di Ma Al-Mustaqim Arang Limbung Kubu Raya - Khotibul Umam (CV Putra Publisher, 2023)
The purpose of this study is to describe and analyze the management of educational facilities. This study uses a qualitative approach with a case study type of research. Data collection techniques with interviews, observation, and documentation. While the data analysis technique is an interactive model analysis technique. The results of this study can be concluded that the management of educational facilities at MA Al Mustaqim Arang Limbung Kubu Raya, namely; means of joint evaluation of educational staff and all teachers, supervising the school principal, obeying school rules that have been set together, controlling the school principal in the learning process and others. Means of learning effectiveness at MA Al Mustaqim Arang Limbung Kubu Raya namely; there is teacher empowerment with various forms of activities to improve student learning. While the obstacles to the effectiveness of the management of educational facilities in increasing student learning at MA Al Mustaqim Arang Limbung Kubu Raya are inadequate teaching staff and many demands from students' parents.